2007
DOI: 10.1111/j.1530-0277.2007.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Ethanol‐Derived Acetaldehyde in the Motivational Properties Induced by Intragastric Ethanol: A Conditioned Place Preference Study in the Rat

Abstract: The ability of 4-MP and DP to decrease EtOH-induced cpp suggests that a reduction of ACD levels is crucial in depriving EtOH from its motivational properties as indexed by the cpp procedure. In addition, this conclusion is supported by the inefficacy of 4-MP in preventing ACD-induced cpp, and by its blockade observed after administration of the selective ACD sequestrating agent DP. The present results underscore the role of EtOH-derived ACD in EtOH-induced motivational properties as well as its abuse liability. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 48 publications
(81 reference statements)
12
102
2
1
Order By: Relevance
“…Similar research has been completed using the compound D-penicillamine, which acts to sequester ACD into a non-reactive stable adduct but does not alter EtOH metabolism. Studies using D-penicillamine have established that sequestering ACD results in a reduction of alcohol intake and a decrease in alcohol conditioned place preference in rats Font et al, 2006b;Peana et al, 2008). D-penicillamine also reduces alcohol conditioned place preference and alcohol induced motor depression in mice (Font et al, 2005;Font et al, 2006a).…”
Section: Alcohol Acetaldehyde and Acetaldehyde Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research has been completed using the compound D-penicillamine, which acts to sequester ACD into a non-reactive stable adduct but does not alter EtOH metabolism. Studies using D-penicillamine have established that sequestering ACD results in a reduction of alcohol intake and a decrease in alcohol conditioned place preference in rats Font et al, 2006b;Peana et al, 2008). D-penicillamine also reduces alcohol conditioned place preference and alcohol induced motor depression in mice (Font et al, 2005;Font et al, 2006a).…”
Section: Alcohol Acetaldehyde and Acetaldehyde Productsmentioning
confidence: 99%
“…Research has shown that both central and peripheral administration of ACD cause an increase in alcohol consumption in rats (Brown et al, 1979;. Rats will exhibit ACD induced CPP and stimulus preference suggesting that ACD is rewarding (Quertemont & De Witte, 2001;Quintanilla & Tampier, 2003;Smith et al, 1984;Spina et al, 2010); blocking or sequestering the formation of ACD resulting from alcohol exposure produces alterations in the neurobiological and behavioral effects of alcohol (Aragon & Amit, 1992;Diana et al, 2008;Font et al, 2005;Font et al, 2006a;Font et al, 2006b;Kaharanian et al, 2011;Koechling & Amit, 1994;Peana et al, 2008). While it is currently difficult to assert that ACD is absolutely necessary for the neurobiological and behavioral actions of alcohol, data show that ACD is likely to be involved to some extent.…”
Section: Acetaldehyde Is Pharmacologically Active In the Cnsmentioning
confidence: 99%
“…For that reason, over the last two decades, repeated proposals have suggested that acetaldehyde derived from the ethanol metabolism generated by the activity of this enzyme plays a role in some of the effects observed after ethanol administration (for extensive reviews, see Quertemont et al 2005;Hipólito et al 2007;Deng and Deitrich 2008). In fact, it has been proven that treatment with acetaldehyde-sequestering agents, after ethanol administration, modifies some ethanol-induced behaviors (Font et al 2005(Font et al , 2006aPeana et al 2008Peana et al , 2009Martí-Prats et al 2010;Pautassi et al 2011). Based on these findings, we speculate that the effect of LA on ethanol-stimulated locomotion is due to a reduction in H 2 O 2 levels, and therefore a lower central rate of acetaldehyde formation owing to a decrease in brain catalase-H 2 O 2 system activity.…”
Section: Discussionmentioning
confidence: 96%
“…Acetaldehyde was also shown to decrease in vivo acetylcholine release in the medial frontal cortex of freely moving rats (Jamal et al 2007b) and to increase in vitro hypothalamic release of β-endorphins (Reddy and Sarkar 1993). In addition, centrally administered or formed acetaldehyde can produce effects similar to ethanol, including increases in locomotion (Arizzi-LaFrance et al 2006;Correa et al 2003) and lever pressing on a low-rate operant schedule , intracranial selfadministration (Brown et al 1979(Brown et al , 1980Rodd-Henricks et al 2002;Rodd et al 2005), and place preference (Smith et al 1984;Peana et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…These effects appear to include some of the emotional and motivational actions that can support ethanol consumption, such as anxiolysis, motor-energizing properties, and preference for a place previously paired with ethanol (Correa et al 2005;Peana et al 2008).…”
Section: Discussionmentioning
confidence: 97%